Phase diagrams in alternative hard materials: Validation of thermodynamic simulation through high temperature x-ray diffraction, differential thermal analysis and microstructural characterization. (June 2021) - de Nicolás, M.; Pereira, L.; Penoy, M.; Bertalan, C.; Useldinger, R.; Llanes, L.; Gordo, E.
Abstract: In this investigation, Ti(C, N)-FeNiCr systems were designed using Thermo-Calc® software. Materials were processed by conventional powder metallurgy, employing different carbon additions to study a wide range of the phase diagram as well as the effect of C in the sintered samples. Specimens were extensively characterised in terms of density, magnetic and mechanical properties, and microstructural features. Simulation approach was validated by means of Differential Thermal Analysis (DTA) and High-Temperature X-Ray Diffraction (HT-XRD), from room temperature up to 1200 °C for each composition, comparing phases obtained for each temperature and composition with predicted ones. Results showed excellent consonance between Thermo-Calc® and XRD phases, except for precipitation of secondary carbides, which appeared in the simulation but not in the sintered samples. Moreover, variation of C content demonstrated to have a direct effect in the microstructural homogenization of the final specimens. Graphical abstract: Unlabelled Image Highlights: Ti(C, N)-FeNiCr cermets were designed with Thermo-Calc® software Materials with different C content were processed by conventional powder metallurgy. Simulation was validated by means of DTA-TG and high-temperature XRD tests. Results showed excellent agreement between predicted and experimental phases. C variation had a direct effect in the microstructure of the final specimens.